2010
DOI: 10.1111/j.1708-8305.2010.00426.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Adherence to Atovaquone‐Proguanil Prophylaxis in Travelers: Table 1

Abstract: Adherence with atovaquone-proguanil malaria prophylaxis is high among travelers from a non-endemic region. Adverse effects are minimal. Non-adherence was primarily attributable to travelers' perception of need.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 18 publications
3
11
0
Order By: Relevance
“…Adherence to chemoprophylaxis found in our study is in agreement with self reported treatment adherence found in other studies, which ranged from 70%–89% for atovaquone-proguanil and 72%–95% for mefloquine [14], [15], [24], [25]. Travelers to Africa were more adherent to chemoprophylaxis, which is also consistent with other studies [14], [20], [26].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Adherence to chemoprophylaxis found in our study is in agreement with self reported treatment adherence found in other studies, which ranged from 70%–89% for atovaquone-proguanil and 72%–95% for mefloquine [14], [15], [24], [25]. Travelers to Africa were more adherent to chemoprophylaxis, which is also consistent with other studies [14], [20], [26].…”
Section: Discussionsupporting
confidence: 93%
“…Travelers to Africa were more adherent to chemoprophylaxis, which is also consistent with other studies [14], [20], [26]. Even though in our travel consultation we do not communicate differences in risk between different high-endemic continents, it is possible that travelers know that malaria risk in Africa is higher than in other continents and therefore are more cautious.…”
Section: Discussionsupporting
confidence: 89%
“…In areas of intense malaria transmission, malaria chemoprophylaxis remains the most important strategy for preventing malaria in travellers [3], but its use may be associated with adverse outcomes and even death [4]. These potentially severe adverse effects may undermine compliant use of malaria chemoprophylaxis in travellers, in particular when considering that these travellers were usually healthy when commencing travel [5-9]. An additional difficulty with malaria chemoprophylaxis is that all drug regimens must be taken meticulously during and for one or more weeks after leaving the malaria-endemic area [10].…”
Section: Introductionmentioning
confidence: 99%
“…Adherence rates varied widely, ranging from 0% for corporate workers placed in Ghana for over a year [27] to 89% for travellers from the USA [31].…”
Section: Adherence Ratesmentioning
confidence: 99%
“…Several studies also reported concerns with side-effects: this included concerns about the safety of long-term use of anti-malarial medication [12,21,40], as well as experienced (both past and present) or anticipated side-effects [15, 21, 23, 26-28, 31, 33, 37, 40, 42]. Other reasons included having too many pills to take [37]; not seeing any mosquitoes [28,37,42]; tiredness [37]; price [23,37,42]; lack of pills [37]; not thinking that prophylaxis was necessary [15,21,31]; being advised (for example, by a tour guide, locals or colleagues) that it was not necessary [15,21,27,31,42] and not liking to take medication [33,37]. A higher perceived risk of catching malaria was associated with greater adherence and having a self-reported low perceived risk [27,42] was associated with poor adherence.…”
Section: Self-reported Reasons For Non-adherencementioning
confidence: 99%